Coccidiosis, Paratuberculosis and Enterotoxaemia in Saudi Goats - Radad, Khaled; Khalil, Sary (Brazilian Journal of Veterinary Pathology, 2011)
During the year 2010, 66 goats suffering from mucoid to hemorrhagic diarrhea were submitted to the Pathology Division, Diagnostic Veterinary Laboratory, Jeddah, Saudi Arabia. After postmortem examination, tissue specimens were obtained from liver, lungs, heart, brain, stomach, small and large intestine and mesenteric lymph nodes for microbiological and histopathological examinations. Data from Microbiology Laboratory revealed that goats had intestinal coccidiosis (34 cases), paratuberculosis (9 cases), enterotoxaemia (22 cases) and mycotic gastritis (1 case). In the present report, we focused on the pathological pictures of the above mentioned diseases in examined goats.